FONPS6, a Nonribosomal Peptide Synthetase, Plays a Crucial Role in Achieving the Full Virulence Potential of the Vascular Wilt Pathogen Fusarium oxysporum f. sp. Niveum - Jiaqi Li; Yanyang Gao; Bowen Li; Li Zhang; Yi Fang; Hongtao Zou; Xuhong Ye (Life)
NPS6 is one of the nonribosomal peptide synthetase (NRPS) family members. The roles of NPS6 in ascomycetes are well known, but its roles in Fusarium oxysporum are unidentified. We investigated its function in the growth, morphology, stress sensitivity, allelochemical secretion, and pathogenesis in F. oxysporum (FoNPS6). The partial deletion of FoNPS6 orthologs (ΔFON-NPS6) resulted in hypersensitivity to H2O2 and KO2, iron depletion, and reduced virulence. Full virulence was restored by complementation. ΔFON-NPS6 not only inhibited spore formation but also displayed hyphal growth patterns that differed significantly from the wild-type strain. Plant leaching released allelochemicals, which FON-NPS6 broke down. All of these findings show that FoNPS6 quantitatively increases F. oxysporum’s pathogenicity.